INTEGRASI ETNOSAINS PINANG DALAM PEMBELAJARAN IPAS SEKOLAH DASAR SEBAGAI UPAYA PENGUATAN LITERASI SAINS BERBASIS BUDAYA PAPUA - Ardian Hangga Kelana; Yongki Dwi Fadhli; Sakka Irawan; Nanita Tabuni; Marice Karubaba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research focuses on efforts to strengthen students' scientific literacy through the integration of areca nut ethnoscience in Natural and Social Sciences (IPAS) learning in elementary schools. Areca nut culture (Areca Catechu) is a crucial part of the lives of the Papuan people and has great potential as a contextual and meaningful learning resource in science learning. Implementing an ethnoscience approach through the use of areca palm plants can bridge scientific concepts with local cultural practices so that students do not feel strange during the learning process. Students can visually understand the function of plant organs and know areca nut as a biotic component (living creature) which has an essential role in the ecosystem. The research method used is descriptive qualitative through observation, interviews and documentation. The results of the research show that the use of areca palm plants in the science and science learning process has succeeded in strengthening students' understanding of the concept of biodiversity, the structure and function of plant organs, and the reciprocal relationship between humans and the environment. Cultural integration in learning also strengthens students' identity and fosters a sense of pride in local Papuan wisdom. This research concludes that the integration of areca nut ethnoscience in science and science learning is effective as a strategy to strengthen local culture-based scientific literacy.